Software size estimation in the early stages of development - Centeno, María Elena (2009)
This paper presents a pilot study that raised the estimate of functional size in the very early stages of software development. The goal is to find a relationship between some measures of artifacts produced in the Requirements Elicitation process such as the Language Extended Lexicon (LEL) and Function Points (FP) of the scenarios. From a set of case studies the respective LELs were measured and the FP of the scenarios were calculated. The values obtained were related using different regression models. The models were object of a rigorous statistical analysis to identify the one that best represents the experimental data based on the values of their statistics. Finally, the model was tested on data collected from three applications that are implemented.